d-Serine Degradation by Proteus mirabilis Contributes to Fitness during Single-Species and Polymicrobial Catheter-Associated Urinary Tract Infection - Aimee L. Brauer (American Society for Microbiology, 2019)
ABSTRACT Proteus mirabilis is a common cause of catheter-associated urinary tract infection (CAUTI) and secondary bacteremia, which are frequently polymicrobial. We previously utilized transposon insertion-site sequencing (Tn-Seq) to identify novel fitness factors for colonization of the catheterized urinary tract during single-species and polymicrobial infection, revealing numerous metabolic pathways that may contribute to P. mirabilis fitness regardless of the presence of other cocolonizing organisms. One such “core” fitness factor was d-serine utilization. In this study, we generated isogenic mutants in d-serine dehydratase (dsdA), d-serine permease (dsdX), and the divergently transcribed activator of the operon (dsdC) to characterize d-serine utilization in P. mirabilis and explore the contribution of this pathway to fitness during single-species and polymicrobial infection. P. mirabilis was capable of utilizing either d- or l-serine as a sole carbon or nitrogen source, and dsdA, dsdX, and dsdC were each specifically required for d-serine degradation. This capability was highly conserved among P. mirabilis isolates, although not universal among uropathogens: Escherichia coli and Morganella morganii utilized d-serine, while Providencia stuartii and Enterococcus faecalis did not. d-Serine utilization did not contribute to P. mirabilis growth in urine ex vivo during a 6-h time course but significantly contributed to fitness during single-species and polymicrobial CAUTI during a 96-h time course, regardless of d-serine utilization by the coinfecting isolate. d-Serine utilization also contributed to secondary bacteremia during CAUTI as well as survival in a direct bacteremia model. Thus, we propose d-serine utilization as a core fitness factor in P. mirabilis and a possible target for disruption of infection. IMPORTANCE Urinary tract infections are among the most common health care-associated infections worldwide, the majority of which involve a urinary catheter (CAUTI). Our recent investigation of CAUTIs in nursing home residents identified Proteus mirabilis, Enterococcus species, and Escherichia coli as the three most common organisms. These infections are also often polymicrobial, and we identified Morganella morganii, Enterococcus species, and Providencia stuartii as being more prevalent during polymicrobial CAUTI than single-species infection. Our research therefore focuses on identifying “core” fitness factors that are highly conserved in P. mirabilis and that contribute to infection regardless of the presence of these other organisms. In this study, we determined that the ability to degrade d-serine, the most abundant d-amino acid in urine and serum, strongly contributes to P. mirabilis fitness within the urinary tract, even when competing for nutrients with another organism. d-Serine uptake and degradation therefore represent potential targets for disruption of P. mirabilis infections.